EVALUASI AKSEPTOR KB SUNTIK 3 BULAN DENGAN SIKLUS MENSTRUASI TIDAK TERATUR DI KLINIK DENKESYAH - Herlina, Lusi; Herawati, Yanti; Wijayanegara, Hidayat (Jurnal Sehat Masada, 2025)
Family Planning is a program that helps married couples to create a happy and prosperous small family by planning for pregnancy and vice versa to avoid unwanted pregnancies, get a birth that is very desirable, set intervals between pregnancies, control the time of birth in relation to the age of the couple and determine the number of children in the family. Midwifery Care in 3-Month Injectable Birth Control Acceptors with Menstrual Cycle Disorders in this study uses an evaluation model developed by Stuflebeam in the 1960s with the CIPP (Context, Input, Process and Product) Evaluation approach developed by the National Study Committee on Evaluation of Phi Delta Kappa. The purpose of the study was to find out the evaluation actions in handling menstrual disorders due to 3-month injectable birth control. This study uses a qualitative approach of a cross sectional design, where the collection of independent variables and bound variables is carried out at the same time. Sampling uses purposive sampling. The population in this study is birth control acceptors who use 3-month injectable birth control. The research was carried out in May 2024. Based on the results of the interview, in the implementation of the evaluation that has been carried out according to the standards. The evaluation of 3-month injectable birth control acceptors is carried out to the maximum, this can be seen from the follow-up to the care provided by providing counseling and counseling related to the use of appropriate contraceptives.